Ex vivo quantification of intracellular pH in Drosophila Malpighian tubule reveals basolateral HCO3−/oxalate exchange through a novel oxalate transporter “Neat” - Rossano, Adam J.; Zhang, Lili; Anderson, Jacob B.; Holmes, Heather L.; Mandal, Asim K.; Decker, James W.; Mount, David B.; Romero, Michael F. (Frontiers in Physiology, 2025)
IntroductionNephrolithiasis is a painful and costly healthcare complication. The most common kidney stones are composed of calcium oxalate and thus renal handling of oxalate is an important facet of understanding the pathogenesis of nephrolithiasis. Recently, the Drosophila melanogaster Malpighian tubule (MT) has emerged as a robust model of trans-epithelial ion transport and nephrolithiasis as MTs readily form luminal calcium-oxalate crystals in the presence of oxalate. Drosophila Prestin (dPrestin, Slc26a6) transports oxalate across the apical surface of the MT into the lumen but a full model of the trans-epithelial movement of oxalate (Ox2−) in the Drosophila MT has been lacking as the basolateral oxalate transporter has remained uncharacterized.MethodsThe objective of this work was to identify and characterize the Drosophila basolateral Ox2− transporter through ex vivo real-time quantification of intracellular pH (pHi) and Xenopus oocyte transport assays.ResultsA putative basolateral oxalate transporter CG5002 (“Neat”) was identified through sequence homology and displayed robust Cl−-independent Ox2− transport and electroneutral Ox2− transport in Xenopus oocytes. pHi in extracted fly MTs was monitored by using the GAL4/UAS system to selectively express pHerry, a pseudo-ratiometric genetically-encoded pH indicator (GEpHI) in the cytosol of the principal cells of the MT. Basolateral perfusion of MTs in CO2/HCO3−-buffered solution produced a large acidification followed by rapid recovery in the transitional segment of the anterior MT. Recovery was interrupted by basolateral application of 1 mM Ox2− or 1 mM SO42. Tissue specific knock-down of Neat with interference RNA (RNAi) reduced the rate of acid-loading in the transitional segment of the MT with regard to Ox2− and SO42−. Knockdown of Neat in the MT also significantly reduced luminal calcium oxalate crystal formation in a fly ex vivo model of calcium oxalate nephrolithiasis.DiscussionThese data indicate Neat is a significant Drosophila basolateral MT oxalate transporter and the basolateral movement of oxalate is functionally coupled to movement of acid equivalents, potentially as Ox2−/HCO3− exchange, Ox2−/OH− exchange, or Ox2−:H+ co-transport.